2022
DOI: 10.3390/polym14122404
|View full text |Cite
|
Sign up to set email alerts
|

Complexation in Aqueous Solution of a Hydrophobic Polyanion (PSSNa) Bearing Different Charge Densities with a Hydrophilic Polycation (PDADMAC)

Abstract: In this work the electrostatic complexation of two strong polyelectrolytes (PEs) was studied, the hydrophilic and positively charged poly (diallyldimethylammonium chloride) (PDADMAC) and the hydrophobic and negatively charged poly (styrene-co-sodium styrene sulfonate) (P(St-co-SSNa)), which was prepared at different sulfonation rates. The latter is known to adopt a pearl necklace conformation in solution for intermediate sulfonation rates, suggesting that a fraction of the P(St-co-SSNa) charges might be trappe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…The bands at 1478 and 1356 cm À1 correspond to asymmetric stretching vibrations of the CQC and C-C bonds in the thiophene ring, respectively. 34 The obtained spectra prove the formation of PEDOT in the structure of microspheres.…”
Section: Investigation Of Edot Polymerization In the Presence Of Poly...mentioning
confidence: 62%
See 1 more Smart Citation
“…The bands at 1478 and 1356 cm À1 correspond to asymmetric stretching vibrations of the CQC and C-C bonds in the thiophene ring, respectively. 34 The obtained spectra prove the formation of PEDOT in the structure of microspheres.…”
Section: Investigation Of Edot Polymerization In the Presence Of Poly...mentioning
confidence: 62%
“…As shown above, the synthesized cross-linked poly(sodium styrene sulfonate) microspheres form a complex with unique features, namely, the permeability to water and aqueous solutions and the developed specific surface due to their porous structure. These characteristics along with the fact that poly (styrene- co -styrene sulfonate) chains have the tendency to adopt a pearl necklace conformation with the formation of hydrophobic domains 34 allowed us to assume that the internal microsphere volume should be more suitable for localization of EDOT monomers. Moreover, taking into account that the general scheme of EDOT polymerization in a polyelectrolyte template implies a charge compensation of the growing PEDOT chain by ionogenic groups of the template, 35 the localization of charge-compensating sulfo groups inside the particles volume apparently also would promote the polymerization of EDOT in the whole microsphere volume.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, despite the influence on the size, all IPECs with different Mw PSS showed the minimum in the radii‐salt concentration dependence described above, indicating that the competition between the primary particles aggregation and the polyanion shell swelling (excess component in IPEC) remains, independent of the Mw of the polyanion. Jemili et al [ 26 ] varied the charge density of PSS via different sulfonation rates and studied IPECs of the respective poly (styrene‐ co ‐sodium styrene sulfonate) (P(St‐ co ‐SSNa)) with PDADMAC at the polycation excess region, polyanion excess region and at the charge equimolarity (1:1) via a number of complementary techniques, including DLS, zeta‐potential measurements, ITC and binding experiments with a dye. It was found that despite the previously proposed pearl necklace conformation of (P(St‐ co ‐SSNa), implying that a number of the charges might be trapped in the hydrophobic domains, close to the equimolar charge concentration the hydrophobic effect responsible for the pearl formation was overcome by the electrostatic interaction, as confirmed by the above‐mentioned techniques indicating the charge stoichiometry of 1:1.…”
Section: Introductionmentioning
confidence: 99%
“…The formation of PECs involves two distinct steps: the generation of primary PECs by ion pairing, followed by their aggregation/reorganization into larger structures. [8][9] When the oppositely charged PE mixture is not at charge stoichiometry, complexation typically results in colloidal polyelectrolyte complexes where the excess PE forms an electrosterically stabilizing shell around the neutral complexed cores 10 with a solvation, charge, hydrophobicity that vary with the molar charge ratio Z([-]/[+]). 9,[11][12][13][14] At charge stoichiometry, when the amount of anionic and cationic charges are equal, two very different situations can occur depending on the strength of the interaction.…”
mentioning
confidence: 99%
“…[8][9] When the oppositely charged PE mixture is not at charge stoichiometry, complexation typically results in colloidal polyelectrolyte complexes where the excess PE forms an electrosterically stabilizing shell around the neutral complexed cores 10 with a solvation, charge, hydrophobicity that vary with the molar charge ratio Z([-]/[+]). 9,[11][12][13][14] At charge stoichiometry, when the amount of anionic and cationic charges are equal, two very different situations can occur depending on the strength of the interaction. When the charged chains are in strong interaction (binding constant kb>10 6 M -1 ), the system undergoes a liquid-solid transition generating aggregates that eventually sediment with time as in the case of the well-known PDADMAC/PSSNa system.…”
mentioning
confidence: 99%